2015
DOI: 10.1016/j.jtcvs.2014.07.105
|View full text |Cite
|
Sign up to set email alerts
|

Standardized approach to valve repair using an expansible aortic ring versus mechanical Bentall: Early outcomes of the CAVIAAR multicentric prospective cohort study

Abstract: A new standardized approach to valve repair, combining an expansible aortic annuloplasty ring with the remodeling technique, presented similar 30-day results to mechanical CVG with a trend toward reducing major adverse valve-related events. Analysis of late outcomes is in process for 3- and 10-year follow-ups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 32 publications
1
24
0
1
Order By: Relevance
“…The safety of VSRR using the remodeling technique and expansible subvalvular annuloplasty has been demonstrated by the CAVIAAR trial showing similar 30-day mortality compared to a mechanical Bentall procedure, with a trend towards more major adverse events in the Bentall group (OR 2.52, P=0.09) (55). At 4 years, crude and propensitymatched analyses confirmed that freedom from valverelated death and freedom from hemorrhagic events are significantly higher after valve repair than replacement; respectively 99% vs. 94% (P<0.001) and 89% vs. 78% (P=0.02), whereas freedom from valve-related reoperation was similar (P=0.22).…”
Section: Aortic Annuloplasty: a Standardised Approach To Av Repairmentioning
confidence: 96%
“…The safety of VSRR using the remodeling technique and expansible subvalvular annuloplasty has been demonstrated by the CAVIAAR trial showing similar 30-day mortality compared to a mechanical Bentall procedure, with a trend towards more major adverse events in the Bentall group (OR 2.52, P=0.09) (55). At 4 years, crude and propensitymatched analyses confirmed that freedom from valverelated death and freedom from hemorrhagic events are significantly higher after valve repair than replacement; respectively 99% vs. 94% (P<0.001) and 89% vs. 78% (P=0.02), whereas freedom from valve-related reoperation was similar (P=0.22).…”
Section: Aortic Annuloplasty: a Standardised Approach To Av Repairmentioning
confidence: 96%
“…It was emphasized, however, that resultant discrepancy of effective height of each cusp should be aggressively corrected for better cusp durability, as described above 27 . He launched a multicenter study of remodeling, and thus the quality of AVP should be reproducible between institutions 44,45 .…”
Section: Standardization Of Aortic Valve-preserving Surgerymentioning
confidence: 99%
“…In addition, the ensuing dedicated and commercially available ring, which was developed and manufactured by Coroneo, Inc (Montreal, Quebec, Canada) in collaboration with Lansac, was first implanted in Europe in a prospective, multicentric clinical trial (CAVIAAR; https://clinicaltrials.gov/ct2/show/ NCT00478803). Early and long-term clinical results from European centers have since been reported [4][5][6].…”
Section: Reply To the Editormentioning
confidence: 99%